ACTIVITIES AND SPACE USE FOR ENABLING LOCAL ECONOMY IN COASTAL LOW INCOME HOUSING - Dewi Septanti; Jouke M. Post; Emilia van Egmond; Masi Mohammadi (Department of Architecture, Institut Teknologi Sepuluh Nopember (ITS), 2012)
Many low income households are supported by Home Based Enterprises (HBE) for their income generation. However the settlements in coastal areas have physical problems related to the corrosive land and climate condition, as well as the possi-bilities of natural hazards such as flooding (ADB, 2003 : UNHABITAT 2003). The rapid growths of cities especially in developing countries (DCs) contribute to social problems, serious burdens for human health and the environment. In order to imp-rove the quality of human life in the coastal cities, some local government decided to remove some settlements to the inland area such as problems in some big coastal cities in Indonesia. In many cases, many resettlements of housing failed to meet community’s and user’s requirements. To reduce and avoid sustainability problems, it is necessary to have more insight and understanding of the used of space in coastal low income housing. This paper describes the use of communal spaces for daily activities which are indicating the lack of space available in coastal settlements in order to accomodate user’s needs.